Systematic literature review in ten years of academic production in Tourism, GIS, Photography and Destinations - Perinotto, André Riani Costa; Walkowski, Marinês; Kumar, Anil (Tourism and Hospitality International Journal, 2024)
The present work aimed to produce a systematic review of the literature on the topics of GIS, Photography, Destinations and Tourism, using literature systematization techniques and bibliometrics. For the analysis, a 10-year scope was used, on the tags: Tourism, Destinations, Photography and GIS, specifically in the period from 2013 to 2023. The analysis was based on the number of articles, citations, relevance and authors. To assist in displaying these results, the software used was VOSviewer and Connected Papers. This topic is essential for tourism, as it is inserted daily in people's daily lives, and thus, it is proven through data and graphs that there are still few publications on the topic. According to what was analyzed, it was possible to observe the lack of works pertinent to the subject and the need for more publications by tourism professionals on the subject researched. The results also showed that bibliometric studies are inexhaustible sources of research, as they easily report branches, the combined use of search software can be allies for tourism research, providing a broader view of which subjects require further study